Chitosan-alginate capsules as oral delivery system for insulin: studies in vitro and in vivo - C. Bürger; S. Maffezzolli; P. Clasen; R.M. Lucinda-Silva; C.A. Rodrigues (São Paulo State University (UNESP), 2008)
The aim of this study was to assess chitosan:alginate capsules as gastric resistant systems for oral administration of insulin. Chitosan:alginate capsules of insulin were tested in simulated gastric and intestinal media and in vivo. The capsules released only about 20% of the insulin after 60 minutes of incubation in simulated gastric medium. On the other hand, almost all the encapsulated insulin was released after being incubated for 90 min in simulated intestinal medium. When capsules containing 20 IU and 40 IU insulin were given to rats by gavage, significantly reduced plasma glucose levels were observed (33.7 % and 51.7%, respectively) two hours after the treatment, which returned to normal after six hours. These results indicate that chitosan:alginate capsules are potential carriers for oral protein delivery.